Erythema nodosum in the course of mycoplasma pneumoniae infection and pregnancy in a 17–year-old patient - Nir, Agnieszka; Szarawarski, Bartosz; Stencel-Gabriel, Krystyna (Journal of Education, Health and Sport, 2023)
Erythema nodosum is the most common form of panniculitis in the paediatric population. It is manifested by painful tumours in shades of red within the subcutaneous tissue, most often within the lower legs. Mild, non-specific systemic symptoms may occur. The course of erythema nodosum is associated primarily with local pain, sometimes implying motor disorders. Erythema nodosum may be primary or secondary as a manifestation of a systemic disease, medication or pregnancy. Although the course is often self-limiting, detecting erythema nodosum requires a systematised diagnosis of potential causative diseases. A detailed medical history and physical examination are vital in this process. Treatment of erythema nodosum most often consists of administering analgesics and anti-inflammatory drugs. Proper causal treatment of the primary disease is more important. The paper presents a case of a teenage girl with an intense course of erythema nodosum, in whom two probable causes of its occurrence were found.